2016
DOI: 10.1007/s10508-015-0687-x
|View full text |Cite
|
Sign up to set email alerts
|

Changing Places and Partners: Associations of Neighborhood Conditions With Sexual Network Turnover Among African American Adults Relocated From Public Housing

Abstract: Neighborhood conditions and sexual network turnover have been associated with the acquisition of HIV and other sexually transmitted infections [HIV/STIs]. However, few studies investigate the influence of neighborhood conditions on sexual network turnover. This longitudinal study uses data collected across 7 visits from a predominantly substance-misusing cohort of 172 African American adults relocated from public housing in Atlanta, Georgia, to determine whether post-relocation changes in exposure to neighborh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Even after adjustment for potential co-founders, informal settlements consistently had higher HIV-prevalence than other settlement types, suggesting there remained unmeasured factors. Housing in informal settlements can be unstable, and studies from North America have highlighted how housing instability is an independent risk factor for HIV and STIs [25]. It may also be that settlement type is a proxy for sexual networks; studies in North America have highlighted how dense sexual networks, shaped by poverty and racism, are crucial for HIV-transmission patterns [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after adjustment for potential co-founders, informal settlements consistently had higher HIV-prevalence than other settlement types, suggesting there remained unmeasured factors. Housing in informal settlements can be unstable, and studies from North America have highlighted how housing instability is an independent risk factor for HIV and STIs [25]. It may also be that settlement type is a proxy for sexual networks; studies in North America have highlighted how dense sexual networks, shaped by poverty and racism, are crucial for HIV-transmission patterns [26].…”
Section: Discussionmentioning
confidence: 99%
“…More widely, this analysis suggests that settlement type may be important in understanding the spatial distribution of HIV in South Africa, and elsewhere. Such spatial patterning of HIV reflects patterns of wider marginalization of those who live there, including race, gender and poverty [1,25,26]. Further investigation into how these factors intersect to shape high HIVincidence and prevalence is critical to understand how best to prevent HIV, and ensure HIVtreatment is available to all.…”
Section: Discussionmentioning
confidence: 99%
“…The number of alcohol outlets in the tract was not associated with partner non-monogamy nor partner risk. Although ecologic studies have found relationships between alcohol outlets and STIs (Cohen et al, 2006; Theall et al, 2009), findings of multilevel studies assessing relationships between alcohol outlets and sexual partnerships in adults have been mixed (Cooper et al, 2015; Linton et al, 2017). It is possible that alcohol outlets indirectly impact women's sexual health by promoting alcohol use and subsequently, higher sexual risk behaviors (Campbell et al, 2009; Cooper et al, 2013; Linton et al, 2017; Linton, Haley, Hunter-Jones, Ross, & Cooper, 2017; Seth, Wingood, & DiClemente, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a stability ratio was calculated for the confidant and sexual networks of ever respondent with two or more study visits. 39,52,53 The stability ratio was calculated as the number of retained ties divided by the original network size.…”
Section: Methodsmentioning
confidence: 99%